Birds of the Negara River Basin, South Kalimantan, Indonesia - Bas van Balen; Crawford Prentice (Indonesian Ornithologists’ Union, 1997)
In January 1989 the wetlands of the Negara and lower Barito river basins (South Kalimantan) were surveyed in order to assess their importance for the conservation of birds. In particular during the last twenty years, logging, reclamation for agriculture and uncontrolled hunting under a growing human population have caused the degradation of these once very rich habitats and subsequently the drastic impoverishment of its bird communities. A total of less than 150 bird species was found. The bird communities of eight habitat types are described. Recommendations are given for the urgent conservation of areas selected amongst the little that is left.